Waste to Valuable by-Product: Kinetic and Thermodynamic Studies of Cd, Cu and Pb Ion Removal by Decanter Cake - Mohd Husin, Mohd Haizal (2010)
Palm oil mills generate about 4 - 5 tons of decanter cake for every 100 tons of palm fresh fruit bunch processed. Due to the high organic content, the decanter cake could be converted to adsorbent for the removal of metal ions from waste water. The decanter cake was first dried at 105oC and then carbonized at 500 oC. Earlier data showed that 500 oC had highest performance in ions removal. The resulting carbonized decanter cake were tested for removing cadmium (II), copper (II), and lead (II) ions. Proximate analysis using thermogravimetry of decanter cake carbonized at 500 oC indicated that the adsorbent contained 4% moisture, 21% volatile, 23% fixed carbon, and 52% ash. Adsorption test was carried out by mixing 1.0 g of the decanter cake in 100 mL aqueous solution of the various ions. Langmuir and Freundlich isotherm models were used to fit the isotherm experimental data. The maximum uptakes of Cd, Cu and Pb onto the carbonized decanter cake in this study were estimated to be 24, 23, and 97 mg/g respectively. The adsorption kinetics was found to follow the pseudo second- order kinetic model. Thermodynamic parameters such as standard enthalpy (delta Ho), standard entropy (delta So) and standard free energy (delta Go) were determined.